Macrophytes and water quality in a large Baltic lagoon: relevance, development and restoration perspectives - Schernewski, Gerald; Friedland, Rene; Paysen, Simon; Bucas, Martynas; Dahlke, Sven; von Weber, Mario (Frontiers in Marine Science, 2023)
We combine historical and recent monitoring data with modeling to get a better insight into water quality development of the large Oder/Szczecin Lagoon and especially the role of macrophytes. Data indicates that the system is eutrophic for centuries and a naturally eutrophic system. During the last decades, external nutrient loads decreased but keep the system in a eutrophic state. The systems primary production is limited by light and nitrogen and cannot be sufficiently managed by external nutrient load reductions. We consider 36% macrophyte coverage of the lagoon area as potential historical maximum. Despite its shallowness the lagoon was never a macrophyte dominated, clear water system. About 31% of the lagoon area would be covered by macrophytes in a good ecological status according to the Water Framework Directive. However, the existing water transparency targets seem too ambitious and not realistic. Changes in macrophyte coverage on water quality are restricted to near shore areas and hardly affect the open lagoon. Existing models require an improved representation of water transparency and effects on macrophyte colonization depth. Presently the patchy macrophyte coverage is only about 12% of the lagoon area. This low coverage and a relatively poor species composition results in a non-satisfactory state classification. However, ecologically valuable angiosperms and charophytes seem to recover. A strict avoidance of mechanical disturbances could be a measure to support macrophyte re-colonization. A systematic improvement of piscivorous fish stocks may be a supporting measure to reduce eutrophication. Restoration perspectives and consequences for environmental policies are discussed.